Vildagliptin and caloric restriction for cardioprotection in pre-diabetic rats - Pongpan Tanajak (2018)
ï¿½ 2017 Society for Endocrinology. Long-term high-fat diet (HFD) consumption causes cardiac dysfunction. Although calorie restriction (CR) has been shown to be useful in obesity, we hypothesized that combined CR with dipeptidyl peptidase-4 (DPP-4) inhibitor provides greater efficacy than monotherapy in attenuating cardiac dysfunction and metabolic impairment in HFDinduced obese-insulin resistant rats. Thirty male Wistar rats were divided into 2 groups to be fed on either a normal diet (ND, n = 6) or a HFD (n = 24) for 12 weeks. Then, HFD rats were divided into 4 subgroups (n = 6/subgroup) to receive just the vehicle, CR diet (60% of mean energy intake and changed to ND), vildagliptin (3 mg/kg/day) or combined CR and vildagliptin for 4 weeks. Metabolic parameters, heart rate variability (HRV), cardiac mitochondrial function, left ventricular (LV) and fibroblast growth factor (FGF) 21 signaling pathway were determined. Rats on a HFD developed insulin and FGF21 resistance, oxidative stress, cardiac mitochondrial dysfunction and impaired LV function. Rats on CR alone showed both decreased body weight and visceral fat accumulation, whereas vildagliptin did not alter these parameters. Rats in CR, vildagliptin and CR plus vildagliptin subgroups had improved insulin sensitivity and oxidative stress. However, vildagliptin improved heart rate variability (HRV), cardiac mitochondrial function and LV function better than the CR. Chronic HFD consumption leads to obese-insulin resistance and FGF21 resistance. Although CR is effective in improving metabolic regulation, vildagliptin provides greater efficacy in preventing cardiac dysfunction by improving anti-apoptosis and FGF21 signaling pathways and attenuating cardiac mitochondrial dysfunction in obese-insulin-resistant rats.